PENANAMAN KESADARAN SEJARAH DAN SIKAP NASIONALISME DALAM PEMBELAJARAN SEJARAH DI SMA NEGERI 2 BANGGAI - Sinyo A Lamato (Universitas Negeri Yogyakarta, 2016)
Abstract: The purpose of the research is to reveal: (1) the reality of historical learning at SMAN 2 Banggai during this time, (2) to know the history of teacher efforts to create awareness of history and nationalism in historical learning at SMA Negeri 2 Banggai, and (3) to know constraints of the history teacher embed the a sense of history and nationalism at SMA Negeri 2 Banggai. The approach method used in this research is descriptive qualitative method. The results showed : (a) learning based on KTSP in SMA 2 Banggai and teachers use varied methods and appropriate media learning materials, (b) instill a sense of history and nationalism in learning history through: (1) approach to students, (2) cultivating history for the development of national culture, (3) teachers more use varied learning methods, (4) implement activities of PPBN, (5) efforts to instill a sense of pride as a nation of Indonesia. Constraints history of teachers instill a sense of history and nationalism in learning history that (1) professionalism of teachers history, (2) limited allocation of time history lesson, (3)lLearning facilities and infrastructure, (4) the attitude of the students in the learning process, (5) the development of communication tools. Keywords: awareness of history, nationalism, historical learning